L’Œuvre d’Orient et l’invention de la tradition française de protection des chrétiens d’Orient - Nathan Jobert (Les Cahiers d’EMAM)
The renewed commitment to the cause of Eastern Christians in France since 2010 has been accompanied by a strong use of a tradition charging France of the protection of Christian communities in the East. This tradition is an “invention”, a historical construction, perpetuated and maintained by certain actors, the most emblematic of which is “l’Œuvre d’Orient”. Created in 1856, “l’Œuvre d’Orient” is a favorable ground for analysing the evolution of a cause that today no longer has the same name than two centuries ago. This article therefore aims to put into perspective the motives for “l’Œuvre d’Orient”’s the creation, the profiles of its founders, its first practices, with the representations and modes of action that circulate but also oppose each other within the current space of mobilization. Thus, certain foundations of tradition, such as the civilising mission of France and the Church in the East, are no longer so highly valued by the very actors who justify their commitment by their desire to perpetuate this heritage.